Atomically resolved interlayer electronic states in complex oxides by using cross-sectional scanning tunneling microscopy. Issue 2 (May 2022) - Huang, Bo-Chao; Hsu, Chun-Chih; Chu, Ying-Hao; Chiu, Ya-Ping
Abstract: Complex oxides show a rich variety of functionalities through their strong coupling to the lattice, electron, orbital, and spin degrees of freedom not only at oxide heterointerfaces but also in layered cuprates. For the topic of oxide heterointerfaces, with advances in growth, delicate tuning of the atomic termination at the interface with layer-by-layer precision is now achievable. The improvements in growth open up opportunities to manipulate the coupling of 3 d electrons at complex oxide interfaces, creating intriguing phenomena that are not attainable in bulk constituents alone. For example, two-dimensional electron gases have been found at LaAlO3 /SrTiO3 heterointerfaces. For the topic of high-temperature layered cuprates (for example, YBa2 Cu3 O6+x (YBCO6+x )), charge order (CO) has been the key to understanding the full picture for high transition temperature superconductors. However, two central questions that involve the general picture of the stacking pattern for the CO interlayer in YBCO6+ x and how exactly the CuO chain influences the CO on the CuO2 plane remain an open issue. Investigating the nanostructure of the CO and its spatial interplay with superconductivity, as well as the relation between CuO2 bilayers and CuO chain layers simultaneously with atomic-scale spatial and energy resolution, is still under debate. Disentangling the physical origins of the interface properties and interlayer electronic states in complex oxides requires an experimentally direct probe localized at the interfaces and characterization of atomically resolved electronic states in oxides. In this paper, we review the utilization of cross-sectional scanning tunneling microscopy (XSTM) and spectroscopy (XSTS) to directly probe electronic states with atomic precision right at and across complex oxide interfaces and interlayers. With this technique, we probe the structural and electronic properties in complex oxides, revealing the underlying detailed electronic structure (e.g., local electronic density of states and ferroelectric polarization in oxide interfaces, as well as the spatial configuration of CO and its interplay with the superconductivity in YBCO6+x ). This forms the basis for an atomic-scale physical understanding of complex oxides, which is also central for designing complex oxide devices. In this review article, the first part gives a brief design idea of the XSTM measurement, a brief description of the cleavage technique, and spectroscopic analysis of XSTM measurements. The second part addresses several models for termination engineering of the electronic states across complex oxide interfaces by using XSTM measurements. The topics to be discussed include the local electronic structure across LaAlO3 /SrTiO3, and ferroelectric polarization-modulated band bending at Nb-SrTiO3 /BiFeO3 interfaces. In addition, the XSTM technique can be used to approach the atomic scale to probe the change in the electronic structure even with atomic layer changes at the interface. This achievement will be demonstrated for the BiFeO3 /La0.7 Sr0.3 MnO3 interface. Furthermore, a precise real-space characterization of the interplay between CO and SC is also addressed using atomically resolved STM/S for cryogenically cleaved YBa2 Cu3 O6.81, which provides direct insights into the work carried out by complex oxide communities using this technique. Finally, a future perspective for the use of XSTM to study complex oxide interface physics will also be addressed.